The Concept of ‘European Relevance’ in RIs: A View from the Humanities - Žic Fuchs, Milena (Array, 2012)
This presentation focused on the relativity of the notion of European relevance in the domain of Humanities research. The diversity of national databases cannot simply be subsumed under "national relevance" since they are both of European and global importance. Special emphasis was placed on the necessity of integrating various types of RIs.